Hardness and Microstructure of a Newly Developed Stainless Steel after Ausforming. Issue 10 (20th March 2017) - Seifert, Merlin; Botzet, Marco; Theisen, Werner
Abstract : In this work, ausforming is applied to a newly developed stainless steel. This process consists of austenitisation, quenching to a deformation temperature above room temperature, deformation of the metastable austenitic microstructure without the formation of martensite, and subsequent quenching in liquid nitrogen. The investigated steel is explicitly developed to be processed by ausforming and manufactured as a laboratory size test melt. The aim is to achieve a steel having a high hardness as well as a high corrosion resistance. Instead of conventional quenching and tempering, conventional processing is followed by ausforming. A parameter study incorporating the austenitisation temperature and time, deformation temperature, deformation speed, and degree of deformation is performed to achieve maximum hardness. Furthermore, the influence of soft annealing prior to ausforming is also investigated. The hardness of ausformed specimens is measured and correlated to the parameters used for processing. The microstructure of selected specimens is also investigated. Surprisingly, small amounts of martensite are found after ausforming, although a hardness of about 600 HV10 is achieved. In fact, a highly deformed austenitic microstructure is found predominantly. Abstract : Ausforming is applied to a new stainless steel designed to combine high hardness and corrosion resistance. A parameter study incorporating several key parameters of ausforming is performed to achieve the maximum hardness. The hardness of ausformed specimens is measured and the microstructure of selected specimens is investigated. Surprisingly, a highly deformed austenitic microstructure leads to a hardness of about 600 HV10.